Study on the Lubricating Characteristics of Graphene Lubricants - Yi Dong; Biao Ma; Cenbo Xiong; Yong Liu; Qin Zhao (Lubricants, 2023)
Graphene is considered a good lubricant additive. The lubricating properties of graphene lubricant at different concentrations and temperatures are studied via a four-ball friction and wear-testing machine. The results show that the coefficient of friction (COF) and wear scar diameter (WSD) of the steel ball with 0.035 wt% graphene lubricant decreased by 40.8% and 50.4%, respectively. Finally, through surface analysis, the following lubrication mechanism is proposed: as the added graphene particles can easily fill and cover the pores of the friction surface, the contact pressure of the rough peak is reduced, resulting in a lower COF and smoother surface. Although the COF increases with temperature, graphene lubricants still exhibit good lubrication effects.